2020
DOI: 10.31729/jnma.4786
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Preventive Practices of Hepatitis B Transmission among Dental Students and Interns in a Tertiary Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Hepatitis B is one of the most common contagious diseases in Nepal and is a signifi- cant public health issue. It is transmitted through contact with contaminated blood or other bodily fluids on broken skin or mucous membranes. Junior doctors and dentists are at particular risk of hepatitis B exposure. This study aims to find the level of knowledge of transmission and prevention of hepatitis B among the dental students. Methods: This was a descriptive cross-sectional study conducted among d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
2
3
1
2
Order By: Relevance
“…Generally, previous studies show that the Nepalese dental students have a high knowledge which may not be different from their medical counterparts. 5,6,10 As dental students and interns formed more than 70% of our study sample, it was not surprising that our findings were in alignment with these past studies conducted among students. However, in contrast to a previous study in which 100% of the study sample reported to understand all the modes of virus transmission, 6 less than half of the participants in our study answered correctly about the possible routes of the virus transmission.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Generally, previous studies show that the Nepalese dental students have a high knowledge which may not be different from their medical counterparts. 5,6,10 As dental students and interns formed more than 70% of our study sample, it was not surprising that our findings were in alignment with these past studies conducted among students. However, in contrast to a previous study in which 100% of the study sample reported to understand all the modes of virus transmission, 6 less than half of the participants in our study answered correctly about the possible routes of the virus transmission.…”
Section: Discussionsupporting
confidence: 89%
“…5,6,10 As dental students and interns formed more than 70% of our study sample, it was not surprising that our findings were in alignment with these past studies conducted among students. However, in contrast to a previous study in which 100% of the study sample reported to understand all the modes of virus transmission, 6 less than half of the participants in our study answered correctly about the possible routes of the virus transmission. This knowledge gap identified among the study participants should be addressed, particularly in continuing infection control education programs for the HCWs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations